Dual-resonance optical fiber lossy mode resonance refractive index sensor - Xupeng Wu; Xiaoshuang Dai; Jian Wang; Haipeng Ren; Xu Wang (PLoS ONE, 2025)
In this paper, we propose a dual-channel surface refractive index sensor based on optical fiber lossy mode resonance (LMR). A multilayer transmission matrix model is constructed to simulate and analyze the optical fiber LMR effect based on two semiconductor oxides, SnO 2 and TiO 2 . Through the rational design of structural parameters, we successfully realize the coexistence of mutually independent LMRs on a single fiber, thereby enabling dual-channel sensing. The dual-channel optical fiber LMR sensor was prepared by electrostatically assembling TiO 2 nanofilms and SnO 2 nanofilms on the sidewall of the optical fiber. The refractive index sensitivity of the dual-channel optical fiber LMR was evaluated via wavelength interrogation, achieving dual-channel refractive index sensing. The refractive index sensitivities are 538.422 nm/RIU and 615.647 nm/RIU in the range of 1.3350 ~ 1.3742. The dual-channel optical fiber LMR refractometer designed in this investigation is a promising platform for the simultaneous detection of multiple protein species and heavy metal ions in biochemical applications.